Acquired resistome and plasmid sequencing of mcr-1 carrying multi-drug resistant Enterobacterales from poultry and their potential transmissibility to humans. (March 2022) - El-Azzi, M.; Sleiman, A.; Fayad, A. Abou; Kassem, I.; Bawazeer, R.; Okdah, L.; Doumith, M.; Alghoribi, M.; Matar, G.
Abstract : Purpose: To investigate the acquired resistome in 18 colistin resistant Escherichia coli isolated from different poultry farms in Lebanon, analyze Inc plasmids associated with mcr, and assess potential transmission to humans. Methods & Materials: A total of 18 E. coli were recovered from poultry feces collected from poultry farms in Lebanon. BMD assay was performed to determine the antimicrobial resistance profiles. Whole-genome sequencing highlighted genetic resistance determinants. Transformation confirmed transmissibility of mcr . Results: BMD results showed that all the 18 isolates were colistin resistant. Transformation confirmed that the plasmids carrying mcr-1 were transmissible. Sequencing showed that ST1140 was the most prevalent. The most frequent resistance determinants were tetA and floR . A total of 15 different plasmid replicon types were identified. The mcr-1 was predominantly located on IncX4 plasmids. Additionally, two isolates harbored the IncI2-type self-conjugative and IncI2-type mcr-1 -harboring plasmids respectively. Conclusion: The findings show that mcr was the most prevalent resistance determinant in multi-drug resistant E. coli isolated poultry farms in Lebanon. The occurrence of mcr on mobile plasmids highlights a risk of transmission to humans.